Microbiology and Nitrogen Cycle in the Benthic Sediments of a Glacial Oligotrophic Deep Andean Lake as Analog of Ancient Martian Lake-Beds - Parro, Victor; Puente-Sánchez, Fernando; Cabrol, Nathalie A.; Gallardo-Carreño, Ignacio; Moreno-Paz, Mercedes; Blanco, Yolanda; García-Villadangos, Miriam; Tambley, Cristian; Tilot, Virginie C.; Thompson, Cody; Smith, Eric; Sobrón, Pablo; et al. (Frontiers in Microbiology, 2019)
Potential benthic habitats of early Mars lakes, probably oligotrophic, could range from hydrothermal to cold sediments. Dynamic processes in the water column (such as turbidity or UV penetration) as well as in the benthic bed (temperature gradients, turbation, or sedimentation rate) contribute to supply nutrients to a potential microbial ecosystem. High altitude, oligotrophic, and deep Andean lakes with active deglaciation processes and recent or past volcanic activity are natural models to assess the feasibility of life in other planetary lake/ocean environments and to develop technology for their exploration. We sampled the benthic sediments (down to 269 m depth) of the oligotrophic lake Laguna Negra (Central Andes, Chile) to investigate its ecosystem through geochemical, biomarker profiling, and molecular ecology studies. The chemistry of the benthic water was similar to the rest of the water column, except for variable amounts of ammonium (up to 2.8 ppm) and nitrate (up to 0.13 ppm). A life detector chip (LDChip) with a 300-antibody microarray revealed the presence of biomass in the form of exopolysaccharides (EPS) and other microbial markers associated to several phylogenetic groups and potential microaerobic and anaerobic metabolisms such as nitrate reduction. DNA analyses showed that 19% of the Archaea sequences corresponded to a group of ammonia-oxidizing archaea (AOA) similar (97%) to Nitrosopumilus spp. (Thaumarchaeota), and 9% of Bacteria sequences to nitrite-oxidizing bacteria (NOB) from the Nitrospira genus, suggesting a coupling between ammonia and nitrite oxidation. Mesocosm experiments with the specific AOA inhibitor 2-Phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide (PTIO) demonstrated an AOA-associated ammonia oxidation activity with the simultaneous accumulation of nitrate and sulfate. The results showed a rich benthic microbial community dominated by microaerobic and anaerobic metabolisms thriving under aphotic, low temperature (4ºC), and relatively high pressure, that might be a suitable terrestrial analogue other planetary settings.